Pembangunan Database Destinasi Pariwisata Indonesia dan Implementasinya pada Sistem Berbasis Web - Hulu, Yosafati (Bina Nusantara University, 2013)
Regarding to: (1) the increasing region’s need in developing tourism destinations; (2) the needs of tourists in selecting appropriate attractions according to specified criteria; (3) the need of travel businesses to offer sights of interest in accordance with the needs of potential tourists, (4) the need to deepen and continue our previous research titled